Familial Peeling Skin Syndrome - ZUHA NAEEM TARIQ RASHID, SADAF FASIH (Journal of Fatima Jinnah Medical University, 2018)
Peeling skin syndrome (PSS) is a rare form of icthyosis with an autosomal recessive inheritance that exhibits superficial painless, continual, or seasonal exfoliation. The syndrome generally appears at birth or in infancy. A 12 year old female child born of consanguineous marriage presented with generalized periodic peeling of skin since 2 years of age. It was associated with itching, seasonal variations and erythema. The child also had mental retardation, attention deficit hyperactivity syndrome and ocular albinism. Her younger brother was also affected from the similar disease.